THE EFFECT OF VAN HIELE LEARNING MODEL TOWARD GEOMETRIC REASONING ABILITY BASED ON SELF-EFFICACY OF SENIOR HIGH SCHOOL STUDENTS - Andi Mariani Ramlan (JME (Journal of Mathematics Education), 2016)
The problem in this research is the low geometric reasoning abilities related to levels that van Hiele level 2 (abstraction ) and level 3 (deduction ) are not achieved its full potential. This research is a quasi experimental design with nonequivalen control group design. This is influenced by the students' ability to reason logically problem remains low, there has been no student's readiness or understanding of mathematical concepts is not optimal. Low student confidence shown from negative attitudes to learning. Based on the results of the study found that: 1) learning model van Hiele had a greater impact than conventional learning models to geometric reasoning abilities of students; 2) learning model van Hiele had a greater impact than conventional learning models to geometric reasoning skills in students who have high self-efficacy; 3) The learning model van Hiele had a greater impact than conventional learning models to geometric reasoning skills in students who have self-efficacy were; 4) There is no influence of van Hiele model of learning and conventional learning models to geometric reasoning skills in students who have low self-efficacy.